Is diaphyseal fixation of short neck-retaining stem prostheses related to the size of the implant?. Issue 2 (March 2021) - Pons-Cabrafiga, Miquel; Arias de la Torre, Jorge; Berlanga-de-Mingo, Daniel; Lobo-Escolar, Luis
Introduction: Short-stem hip prostheses present variable proximal femoral bone radiological findings. The aims of this study were to analyse, in our patients with implanted collum femoris-preserving (CFP) stems, cancellous bone remodelling, cortical distal hypertrophy and pedestal formation, and the relationship between those radiological changes that suggest distal fixation with the size of the stem. Methods: From October 2001 to December 2012 a total of 199 consecutive primary total hip arthroplasties in 180 patients were performed at our department using the CFP stem and followed up for a minimum of 5 years until December 2017. Results: Stress shielding was present in 74% of oversized stems cases, but in normal or undersized stems, stress shielding was present in 8.5%. Cortical hyperthrophy was observed in 49% of the oversized stems and in 6% of the normal or undersized ones. Finally, non-statistically significant differences ( p   =  0.089) in pedestal formation were found, present in 16.3% of the oversized stems and in 6% of normal or undersized ones. Conclusions: Oversized stems cause more stress shielding and distal cortical hypertrophy in the distal part of the stem, which indicates distal fixation in bigger sizes of stem.